2020
DOI: 10.1021/acs.orglett.0c03546
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxyl Catalysts for Six-Membered Ring Bromolactonization and Intermolecular Bromoesterification of Alkenes with Carboxylic Acids

Abstract: We developed a nitroxyl-catalyzed bromoesterification of alkenes with bromo reagents, which includes a sixmembered ring bromolactonization of alkenyl carboxylic acids catalyzed by AZADO as the nitroxyl radical catalyst, and an intermolecular bromoesterification of alkenes with carboxylic acids using NMO as the N-oxide catalyst. We also accomplished a remote diastereoselective bromohydroxylation via an AZADO-catalyzed six-membered ring bromolactonization and a subsequent ring cleavage reaction with alkylamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Based on the above results and previous reports 76,86 , a plausible mechanism of present TEMPO catalysis is proposed (Fig. 9).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Based on the above results and previous reports 76,86 , a plausible mechanism of present TEMPO catalysis is proposed (Fig. 9).…”
Section: Resultssupporting
confidence: 77%
“…In this work, TEMPO + and its derivatives, which could be generated in situ from commercially available TEMPO [83][84][85][86] and electrophilic halogenating reagents, were developed as diverse and efficient catalysts in various halogenation reactions. Besides bromonium and iodonium, the chloronium was also strongly activated by catalytic amount of TEMPO + .…”
mentioning
confidence: 99%
“…In 2021, Moriyama et al first revealed the Lewis acidity of oxoammonium species using computational evidence. 236 They reported that AZADO catalyzes the bromolactonization of alkenes with NBS. They computationally proposed that an in-situ generated oxoammonium species activated NBS upon coordination to the carbonyl group on the nitrogen center.…”
Section: -8-3 Other Oxidative Transformations (Scheme 38)mentioning
confidence: 99%
“…32b Recently, Matsubara has developed a trans-cyclooctene catalyst 26 for the bromolactonization of olefinic acid 24 to give lactone 25. This method makes use of the sterically protected alkene to facilitate the transfer of an electrophilic bromine from N-bromoacetamide to the alkene substrate via the bromiranium species F. 33 Some other examples of new catalyst/promoter developments for electrophilic bromination reactions include the use of iodobenzene derivative 27, 34 morpholine-HFIP salt, 35 nitroxyl 28, 36 indole 29, 37 and zwitterion 30. 38 The discovery of novel bromine carriers has also played a critical role in the advancement of these bromination reactions.…”
Section: Some New Catalysts and Reagents For Brominationmentioning
confidence: 99%